2000
DOI: 10.1038/sj.onc.1203726
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast growth factor (FGF) signaling through PI 3-kinase and Akt/PKB is required for embryoid body differentiation

Abstract: The role of FGF signaling in early epithelial di erentiation was investigated in ES (embryonic stem) cell derived embryoid bodies. A dominant negative ®broblast growth factor receptor (FGFR) mutation was created by stably introducing into ES cells an Fgfr2 cDNA, truncated in its enzymatic domains. These cells failed to di erentiate into cystic embryoid bodies. No epithelial di erentiation and cavitation morphogenesis could be observed, in the mutant, although its rate of cell proliferation remained unchanged. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
91
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(100 citation statements)
references
References 48 publications
8
91
1
Order By: Relevance
“…is independent of the well established PI3K-Akt signaling pathway utilized by most peptide growth factors such as IGF-1, EGF, and other FGFs (25)(26)(27)(28). Instead, our data provide evidence to show that activation of S6K1 is directly mediated by mTOR.…”
Section: Discussioncontrasting
confidence: 45%
See 1 more Smart Citation
“…is independent of the well established PI3K-Akt signaling pathway utilized by most peptide growth factors such as IGF-1, EGF, and other FGFs (25)(26)(27)(28). Instead, our data provide evidence to show that activation of S6K1 is directly mediated by mTOR.…”
Section: Discussioncontrasting
confidence: 45%
“…Furthermore, phosphatidylinositol 3-kinase (PI3K)/Akt/p70 ribosomal S6 kinase (S6K1) cascade also play important roles in mediating FGFR signaling. Activation of PI3K by FGF-FGFRs has been demonstrated in studies using biochemical, pharmacological, and genetic approaches (25)(26)(27)(28). Results from these studies suggested that PI3K can be activated directly via association with FRS or indirectly via an Erk-dependent pathway (27,29).…”
mentioning
confidence: 99%
“…Stk40 Induces ESC Differentiation Through Activation of the Erk/ MAPK Pathway. Experimental evidence suggests that multiple signaling pathways including the Erk/MAPK, TGF-β, and PI3K pathways might be involved in ExEn development (4,(20)(21)(22). Using inhibitors of these pathways, we found that only the Mek1/ 2 inhibitor (U0126) abrogated Stk40-induced ESC differentiation, which was determined by both cell morphology and Sox7 expression (Fig.…”
Section: Forced Expression Of Stk40 Induces Esc Differentiation Into mentioning
confidence: 88%
“…Cumulative evidence on mESCs consistently revealed that the interaction between FGFs and their receptors led to the upregulation of ECM molecules through the activation of PI3K/Akt/PKB [27,28], and that this promoted basement …”
Section: Discussionmentioning
confidence: 99%